2015
DOI: 10.1007/s00210-015-1165-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of host β1- and β2-adrenergic receptors in a murine model of B16 melanoma: functional involvement of β3-adrenergic receptors

Abstract: Complex interactions between tumor cells and their surrounding compartment are strongly influenced by the host in which the tumor grows. In melanoma, for instance, stress-associated norephinephrine (NE), acting at β-adrenergic receptors (β-ARs), stimulates melanoma cell proliferation and tumor angiogenesis. Among β-ARs, β3-ARs play a role acting not only at tumor cells but also at non-neoplastic stromal cells within the melanoma. In the present study, we used a murine model of B16 melanoma to evaluate the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…Here, we show that propranolol administration in immunocompetent mice has no effect on B16F10 tumour angiogenesis but increases tumour arteriolar remodelling at the highest dose. This result is in accordance with the observation that genetic deletion of β 1/2 ‐adrenoceptors increases tumour vascularization in the B16F10 melanoma model (Sereni et al , ). Conversely, a recent study performed in immunodeficient mice showed that propranolol administered in drinking water decreases intratumour vessel density in a preclinical model of human melanoma (Wrobel and Le Gal, ).…”
Section: Discussionsupporting
confidence: 92%
“…Here, we show that propranolol administration in immunocompetent mice has no effect on B16F10 tumour angiogenesis but increases tumour arteriolar remodelling at the highest dose. This result is in accordance with the observation that genetic deletion of β 1/2 ‐adrenoceptors increases tumour vascularization in the B16F10 melanoma model (Sereni et al , ). Conversely, a recent study performed in immunodeficient mice showed that propranolol administered in drinking water decreases intratumour vessel density in a preclinical model of human melanoma (Wrobel and Le Gal, ).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, considering the serious adverse effects observed in newborns receiving oral propranolol with plasma concentrations around 20 ng/mL, this value is currently considered a sort of safe cut-off value [55]. For this reason, if the mean propranolol plasma concentration will be less than 20 ng/ml, as expected, the treatment with propranolol eye drops should be considered safe, being unable to cause high plasma levels of propranolol.…”
Section: Methods: Data Collection Management Analysismentioning
confidence: 99%
“…The hypothesis that the insensitivity to propranolol of 129S6 mice was due to the preponderance in this strain of β3-ARs, that are minimally blocked by propranolol [51], was confirmed by the discovery that this receptor is involved in VEGF production in hypoxic retinas, through the nitric oxide pathway [52]. The discovery of a proangiogenic action of β3-ARs suggested to investigate a possible role for this receptor also in cancer growth [5355], a new frontier of research currently for neonatologists.…”
Section: Introductionmentioning
confidence: 99%
“…The possible pro‐tumourigenic role of β 3 ‐adrenoceptors has been confirmed by some findings obtained in a mouse model of melanoma in which syngeneic B16F10 cells have been inoculated in mice with β 1 ‐ and β 2 ‐adrenoceptor gene deletion (β 1 /β 2 ‐adrenoceptor knockout; Sereni et al ., ). This model has contributed to reveal an important role for host β 1 ‐ and/or β 2 ‐adrenoceptors in regulating the levels of catecholamines and β 3 ‐adrenoceptors in the tumour mass.…”
Section: Role Of β3‐adrenoceptors In Melanomamentioning
confidence: 97%
“…So far, the role of β 3 ‐adrenoceptors in melanoma has been poorly studied, although some preclinical data demonstrate that these receptors may participate in melanoma progression suggesting that blocking β 3 ‐adrenoceptors may be a relevant treatment for melanoma (Dal Monte et al ., ; Dal Monte et al ., ; Calvani et al ., ; Sereni et al ., ). However, the limited understanding of β 3 ‐adrenoceptor function and the poor pharmacological profile of the β 3 ‐adrenoceptor blockers currently available have hampered the development of clinical studies, thus making it difficult to extrapolate results from preclinical studies to humans.…”
Section: Introductionmentioning
confidence: 97%